Green and clean campus melalui sosialisasi pengelolaan sampah dan limbah organik terpadu berkelanjutan: Green and clean program through socialization sustainable integrated waste management and composting - Ikawati Karim; Widyanti Utami A.; Andi Werawe Angka; Kasmiati Kasmiati; Andi Mawadda Zakiyah; Weni Anggraini Adhisty; Muhammad Nasir Badu (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2026)
Waste is one of the main issues in environmental pollution. Therefore, ineffective and inefficient waste management can potentially damage the environment, such as waste decomposition, which causes health risks. Universitas Sulawesi Barat as the locus of ongoing activities, experiences various problems in its waste management. The large amount of waste scattered on campus is due to the lack of awareness of stakeholders, including students and canteen managers, as the largest contributors to waste. The absence of garbage pickup trucks on campus has made waste management ineffective, and waste is often burned on campus, which can have serious health impacts if the smoke is inhaled. Therefore, various stages of program activities were carried out from July to September 2025, starting with program socialization to stakeholders, namely PT. Kencana Hijau Bina Lingkungan (KHBL) Polewali Mandar, conducting socialization with the theme "Zero Waste: Green and Clean Campus" at Universitas Sulawesi Barat by presenting students, canteen managers, and staff of the State-Owned Agency (BMN) Unsulbar as those responsible for campus waste management. In addition to presenting an audience of students, canteen managers, and BMN, it also presented speakers from PT. KHBL Polewali Mandar, the Department of Environment and Sanitation (DLHK) of Majene Regency, as well as speakers from Unsulbar lecturers regarding the role and function of BMN in waste management, the role and function of students in waste management, and the role and function of canteen managers in campus waste management.